Physical Education in the 21st century: An integrative review of its innovative characteristics - Leao Pereira, Ana Flávia; Lorente-Catalan, Eloisa; Anastácio Oliveira, Taciany Cristina (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study aimed to identify the innovative characteristics of 21st-century school PE through an integrative literature review. The descriptors used were "Physical Education," "21st century," and "innovation" in English, Spanish, and Portuguese, covering the period from 2010 to 2020 in the Eric, Dialnet, Scielo, and Capes databases. A deductive content analysis was conducted on the final 38 selected articles, organizing the identified characteristics into four analytical categories (axes) and 18 subcategories (criteria). Regarding the first axis (subject objectives), the study showed that 21st-century Physical Education (PE) places students at the center of their learning process, emphasizing "learning to be, to know, and to live together" through "learning by doing" within the manifestations of motor culture. Regarding the second axis (methodology), the literature recommends using active methodologies that develop life skills through meaningful, authentic learning situations that engage students in a competence-based and holistic manner. It is also suggested that these learning experiences be linked to social reality and approached from a critical and post-critical perspective. Concerning the third axis (assessment), a formative and shared assessment throughout the teaching-learning process is advocated. Finally, in terms of institutional management (fourth axis), an open and flexible approach is deemed necessary, extending beyond the school walls through collaborations with the broader community.